Formation of plasma electrons’ flows in the homogeneous beam-plasma system - Tanygina, D.M.; Anisimov, I.O.; Levitsky, S.M. (Вопросы атомной науки и техники, 2011)
1D simulation of the beam-plasma interaction demonstrates formation of quasi-periodical flows of background plasma electrons. Flows directed along the electron beam velocity have larger velocities comparing with the flows directed in the opposite side. This effect is associated with plasma electrons’ acceleration under the pressure of the inhomogeneous HF electric field excited during the development of the beam-plasma instability. At the same time, accelerated electrons moving parallel to the beam’s direction can interact with the excited Langmuir wave via mechanism of Landau damping.